Applications used as Campus Wide Information System - Seema Johar (International Journal of Advanced Science and Technology, 2020)
Since time immemorial the humans have found a way to communicate. And now in the age where we have entered a digital world all applications and websites are centred on in communicating information whether formal or informal. The purpose of the study is to analyse the various existing tools that could be used as a campus wide information system. The main focus is to analyse whether web-based sites such as Facebook, YouTube and internet-based mobile applications such as WhatsApp, Viber etc. are being used as an unofficial tool for CWIS and if not, would it have a possibility of being an efficient tool for a campus wide information system.